(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
The article presents the results of a comparative research on the sources of law and on the main features any constitutional state should be based on when ruling on life sciences. Facing uncertain and ever-changing scientific outcomes, on the one hand, and the moral importance of every decision to be taken, on the other hand, are very difficult challenges for every legal actor (mainly parliaments and courts) dealing with life sciences. Biolaw in general has to be capable to assure a tailored approach to every single case and to avoid static and fundamentalist approaches while promoting, at the same time, the maximum degree of equality and rationality and a sustainable level of predictability. Basing the reasoning on the very nature of the object to be regulated (i.e. life sciences) the Author singles out the main traits of a biolaw able both to take into account the features of evidences stemmed from life sciences and to promote pluralism and fundamental rights.